Quantification of Serum IgG Subclasses by Use of Subclass-Specific Tryptic Peptides and Liquid Chromatography–Tandem Mass Spectrometry. (1st August 2014) - Ladwig, Paula M; Barnidge, David R; Snyder, Melissa R; Katzmann, Jerry A; Murray, David L
Abstract: BACKGROUND: Measurement of IgG subclasses is a useful tool for investigation of humoral immune deficiency in the presence of total IgG within reference intervals and IgG4-related disease. Nephelometry has been the method of choice for quantification. We describe an LC-MS/MS method that can multiplex all 4 subclasses along with total IgG by use of either IgG subclass-specific peptide stable isotope–labeled internal standards or a surrogate digest standard for quantification and does not rely on antigen/antibody reactions. METHODS: We combined serum with labeled internal peptide standards and intact purified horse IgG. Samples were denatured, reduced, alkylated, and digested. We analyzed the digested serum by LC-MS/MS for IgG subclasses 1–4 and total IgG. RESULTS: We assayed 112 patient sera by LC-MS/MS and immunonephelometry. The mean of the slopes and R 2 values for IgG1, IgG2, IgG3, IgG4, and IgG were 1.18 and 0.93, respectively. Interassay imprecision for the LC-MS/MS method was <15% for total IgG and subclasses and was slightly improved by use of a calibrator peptide from an exogenous horse IgG. Summed total IgG correlated with the measured total IgG within 10%. Reference intervals and analytical measuring range were all similar to our previous validation data for the immunonephelometry assays. CONCLUSIONS: Total IgG and IgG subclasses 1, 2, 3, and 4 can be quantified by LC-MS/MS with performance comparable to nephelometry.